2019
DOI: 10.24874/pes01.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Coarse Rapeseed Oil Additivated With Nanoparticles of Zinc Oxide

Abstract: Particles of ZnO have 145 nm. The rapeseed oil was supplied by Expur SA Bucharest. For the tested ranges of the parameters, the additivation of rapeseed oil with ZnO does not improve the friction coefficient, but the wear rate of WSD seems to be less sensitive for the more severe regimes when the vegetal oil is additivated. The additivation of rapeseed oil with ZnO is still efficient for the tested ranges of load and speed as compared to the neat rapeseed oil, but there is visible that friction coefficient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Many investigators have reported the thermal enhancement and tribological improvement of mineral and synthetic refrigeration oil and bio lubricants with and without the addition of nanoparticles and concluded that the inclusion of nanoparticles to refrigeration oil leads to the reduction in power consumption, lower friction coefficients and enhancement in COP [14][15][16][17][18]. However, the inclusion of nanoparticles in lubricants, contribute to copious problems such as clogging, sedimentation and erosion and reasons for significant enhancement with nanoparticles at different concentrations are also unclear [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have reported the thermal enhancement and tribological improvement of mineral and synthetic refrigeration oil and bio lubricants with and without the addition of nanoparticles and concluded that the inclusion of nanoparticles to refrigeration oil leads to the reduction in power consumption, lower friction coefficients and enhancement in COP [14][15][16][17][18]. However, the inclusion of nanoparticles in lubricants, contribute to copious problems such as clogging, sedimentation and erosion and reasons for significant enhancement with nanoparticles at different concentrations are also unclear [19].…”
Section: Introductionmentioning
confidence: 99%